2022
DOI: 10.1186/s12864-022-08300-6
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles in Malpighian tubules of the vector leafhopper Psammotettix striatus (L.) revealed regional functional diversity and heterogeneity

Abstract: Background Many leafhoppers are known as pests and disease vectors of economically important plants. Previous studies of the physiological functions of vector leafhoppers have mainly focused on the salivary glands and the alimentary tract that are deemed to be associated with digestion, host defense and phytoplasma and/or virus transmission. By contrast, the significance of Malpighian tubules (MTs) is less studied. To clarify the physiological function of MTs of the vector leafhopper Psammotett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…In this study, Pantoea was found to be the most abundant bacteria in the Malpighian tubules of R. dorsalis fifth-instar larvae. The Malpighian tubules are the primary excretory organs of leafhoppers, responsible for the formation of primary urine and the elimination of metabolic waste [ 66 ]. Our unpublished study has shown that Pantoea bacteria in R. dorsalis play a crucial role in the recycling of nitrogenous waste.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Pantoea was found to be the most abundant bacteria in the Malpighian tubules of R. dorsalis fifth-instar larvae. The Malpighian tubules are the primary excretory organs of leafhoppers, responsible for the formation of primary urine and the elimination of metabolic waste [ 66 ]. Our unpublished study has shown that Pantoea bacteria in R. dorsalis play a crucial role in the recycling of nitrogenous waste.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the Malpighian tubules of leafhoppers lack any structures for storing brochosomes, suggesting that these are stored inside cells until they are quickly discharged into the lumen and pumped through the proximal parts of the Malpighian tubules to the hindgut and rectum shortly before the leafhopper extrudes droplets of secretory fluid and applies them onto the body surface [ 3 ]. In leafhoppers such as Psammotettix striatus (Linnaeus 1758) and Graphocephala fennahi (Young, 1977), studies have demonstrated that the brochosomes released into the Malpighian tubule lumen in a cytosolic-like manner through BVs merge with the apical plasma membrane [ 18 , 21 , 23 , 24 ]. However, this “exocytosis” process seems applicable only to brochosomes housed within vacuoles situated near the plasma membrane periphery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, due to the continuous shedding of brochosomes during the grooming process and in daily activities, this anointing behavior might be repeated multiple times between two molts to replenish the shed brochosomes on the body surface [ 6 , 20 ]. Previous research has suggested that brochosomes merge with the apical plasma membrane through brochosome-containing vacuoles and are released into the lumen, following a process similar to exocytosis [ 18 , 21 , 23 , 24 ]. Additionally, the leafhopper’s Malpighian tubules lack a dedicated storage structure for brochosomes.…”
Section: Introductionmentioning
confidence: 99%
“…AMP transcripts are actually constitutively expressed in D. melanogaster tubules, and AMP production, which is upregulated several fold in response to an immune challenge, relies upon the IMD pathway and is independent of the Toll pathway ( 40 ). In Aedes aegypti Malpighian tubules, upregulation of the Toll pathway results in the expression of immune effectors, including AMPs ( 22 ), and in the leaf hopper Psammotettix striatus , AMPs are highly expressed, but differentially, in regions of the Malpighian tubules ( 41 ).…”
Section: Immunitymentioning
confidence: 99%